Persepsi Hadis Taqwa Dengan Metode Tematik - Abustani Ilyas; Erwin Hafid; Fahruddin Fahruddin; Sitti Khadijah Amran; Haswani Ansar; Nana Nur Zulaikha (PT. Banjarese Pacific Indonesia, 2026)
Taqwa secara epistemologi berasal dari bahasa Arab